Discovery of Factors Influencing Marital Dissatisfaction in Spouses of Military Personnel - Eftekhari , Mohammad Mahdi; Shirvani, Fatemeh; Fathi Kilisani, Zahra; Mosayeb Khozani, Raheleh (Applied Family Therapy Journal (AFTJ), 2025)
ABSTRACTObjective: The present study aimed to identify the factors influencing marital dissatisfaction among spouses of military personnel.Method: This study employed a qualitative research design, and data were collected through semi-structured interviews. The statistical population consisted of spouses (women) of military personnel residing in the city of Isfahan in 2025. The participants were selected using purposive sampling. After conducting interviews with 12 spouses (women) of military personnel, the factors influencing marital dissatisfaction were identified and data saturation was achieved. Data analysis was performed using the thematic analysis method proposed by Stirling (2001), and the themes were categorized into three levels: basic, organizing, and global themes.Findings: Based on the findings of the study, the basic themes comprised 50 concepts, the organizing themes included 11 concepts, and the global themes were classified into three overarching categories entitled individual factors, spouse-related factors, and spouse’s occupational factors, which were identified and extracted.Conclusion: According to the results of this study, identifying and understanding the factors influencing marital dissatisfaction among spouses of military personnel can contribute to the reduction of marital dissatisfaction and enhance individuals’ awareness of the issues and challenges associated with marriage to military personnel in premarital counseling.